Modeling of undergraduate student attrition and retention using HMM - Denoga, Gay Marie C. (2003)
In this thesis, student performance at the undergraduate level of the Department of Electrical and Electronics Engineering (EEE) was modeled using Hidden Markov Models (HMMs). These HMMs were developed using data based on academic records from Academic Year (AY) 1991 to AY 1997 and corresponding to students taking up BS Computer Engineering, BS Electrical Engineering, and BS Electronics and Communications Engineering students who entered the University of the Philippines Diliman as Freshmen from AY 1990 to AY 1996. Two experiments were conducted to determine the optional feature vectors that should be used to train the HMMs. Candidate features investigated in these experiments are the set of subjects taken by students, thier final grades in these subjects, the number of times that a student takes a particular subjects, averaged grades of students, and the combination of final grades and subjects taken per semester. The Hidden Markov Models developed in this thesis may be used to predict the probability that a certain student will graduate or will not graduate, and what the probable attrition or retention rate will be for a batch of students based on grades in certain courses. These HMMs will be able to provide additional basis for Readmission Committee decisions regarding appeals of delinquent students, and for the formulation of student retention policies.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: University of the Philippines (Diliman) -- Department of Electrical and Electronics Engineering -- Students; Markov processes; College students -- Rating of -- Philippines -- Diliman (Quezon City).; Prediction of scholastic success -- Experiments